Innovative Curriculum Design Based on Local Wisdom: Integrating Bengkalis Folktales into Language and Character Education in High Schools - Mukminati Zulfa; Harjito Harjito; Nazla Maharani Umaya (Universitas Pendidikan Mandalika, 2026)
This study aims to develop an innovative curriculum model based on local wisdom in Bengkalis by integrating Malay cultural values into Indonesian language learning at the senior high school level. The research employed a Research and Development (R&D) method adapted from the ADDIE model, encompassing the stages of needs analysis, design, development, expert validation, and limited implementation. The implementation was conducted at SMAS IT Mutiara Pinggir and SMAS Alam Duri in Bengkalis Regency. Data were collected through expert validation instruments, observation guidelines, questionnaires, and interviews. Data analysis involved descriptive quantitative techniques to assess the feasibility of the curriculum model and qualitative thematic analysis to explore teachers’ and students’ learning experiences. The validation results indicate that the developed model demonstrates a very high level of feasibility, with an average score of 4.43. Findings from the limited implementation reveal increased student engagement and the strengthening of character values through learning activities based on local folklore, including Bujang Ikal, Lancang Kuning, and Laksamana Raja di Laut. The integration of Contextual Teaching and Learning (CTL) principles with character education contributes to Indonesian language learning that is more contextual, reflective, and meaningful. Furthermore, the proposed curriculum model aligns with the objectives of the Merdeka Curriculum and the Pancasila Student Profile policy, and it can be replicated in other regions with appropriate adaptations to local cultural contexts. Overall, the findings confirm that curriculum development grounded in local wisdom is an effective strategy for preserving cultural values while simultaneously strengthening character education in schools.